Health and economic impact of a smoking cessation program in Korean workplaces. (5th July 2022) - Kim, Soo Kyoung; Lee, Jeongeun; Lee, Jaeun; Ahn, Jeonghoon; Kim, Hyekyeong
Abstract: Smoking is a leading cause of diseases and death, with significant socioeconomic consequences. The purpose of this study was to evaluate the health and economic effectiveness of a workplace smoking cessation program. A total of 89 smokers from seven workplaces in Korea were the participants of the program. For 4 months, individual counseling based on the transtheoretical model (TTM) was conducted and interpersonal and organizational components were applied to encourage entire workplaces to encourage employee smoking cessation. The primary outcome was whether participants quit smoking or not. We also evaluated the changes in attitude and perceptions related to smoking cessation before and after the program and estimated the program's economic effects. Economic effects were defined as reductions in productivity losses and medical expenses. We calculated the return on investment (ROI) values representing the averted cost through the program compared to program cost. At the end of the program, 40.4% of participants quit smoking. Improvements were observed in TTM-based attitudes and perceptions. The mean reduction in productivity losses was estimated to be $187, 609.94 for 2 yr and the mean reduction in medical expenses was $3, 136.49 at 20 yr among seven workplaces. When accounting for these reductions, the ROI was 15.39 (ranging from ‐1.00 to 44.53). These effects were robust under various scenarios. The smoking cessation program should be expanded to a wider variety of workplaces. In the future, more sophisticated economic assessment methods should be developed and applied to facilitate workplace recruitment and attract management support. Lay Summary: Smoking is a major cause of disease and death with large socioeconomic costs. This study examined the effect of a workplace smoking cessation program on health perspective, and on productivity and profit. A total of 40.4% of participants quit smoking, and the perceptions on smoking were improved. Also, the program was revealed to have an average return on investment (ROI) of 15.39. This can be deemed as the program's economic effect is 15.39 times the program cost. We believe this kind of evaluation may help with the dissemination of workplace health promotion programs.